You are on page 1of 19

# 1

:
} {an , L >0
n0 n>n0 .|an L|<lim(an) = L :
n
:

} {an , M n0
() lim ( an < M
n>n0 .an>Mn an ) = :
n
:
} {an {nk}- k ,
. bk = ank } ,{bk }.{an
:
.1 .
.2 ) (.
.3 an ,L- | |an ) |L|- (.
c ,lim(bn)=B ,lim(an)=A .4
lim(chan)=chA
lim(bn+an)=A+B
lim(anhbn)=AhB
bn 0 , B 0 ) lim(an/bn)=A/B ( n
.5 } {bn ) ( {an}- ,0- } {anhbn .0-
{an} .6 b ,L- . , n0 an>b ,n>n0
.L>b
.7 } {an {bn}- an>bn - ,n ).lim(an) > lim(bn
.8 ' {bn} ,{an} - {cn}- . lim(an)=lim(cn)=L
, n0 cn>bn>an ,n>n0 } {bn . lim(bn)=L -
.9 } {an 0- ,0- | 1/|an .

.10 .
.11 .
.12 {an} - {bn} , ,
an<bn n ,lim(bn-an)=0 - .
"" {[an,bn]} :
) lim(bn-an)=0 - ,(0-
c [an,bn]c - .n
.13 } {an ) ( ,
. : ,
.
.14 -Bolzano-Weierstrass ) (
.

:
.1 ' ) (.
.2 {an} - . lim( an +1 an )=q an q<1 : 0-
) (

an q>1 -

q=1

## .3 {an} - . lim( n an )=c an c<1 : 0-

an c>1 -

c=1
an +1
.4 -n {an} - . )
an

an +1
) )= lim( n an
an

( lim } { n an

(.lim

, -n .1-

.5 -
0

.
an

k
k
.6 , lim 1 + = e -e an- .
an

.7 // .

:
D ,E ) ,( E , D f
D E Dx
.Ey
f: D E , f(x)=y :
z : D .f
z E .f
z x .f
z y .f
z x ,f(x)=y ,y y- .x
.
- ) f(x " / .
) f(x.
- f: D E , " .D
(image) Im( f ) = { f ( x) | x D} :
- ) y=f(x D
M f ( x) < M . x D
-- )"( - " f: D E :
) f(x1)=f(x2) x1=x2 x .(y
- ) ,(E ,Im(f)=E y E
. x D -

) I(x)=x , I: D D - " (.
f: C D -
g: D E

:f

g):C E
) )g ) ( x) = g ( f ( x

(f
(f

.f: C D - g: D C g f = I C-
f g = I D f(x)- g(x)- .
" .g(x)=f -1(x) :

## -Heine ) f(x ,x=a

) , , x=a( , L ) f(x x
.a-( f ( x) ) = L :
. lim } a xn ,{xn ,n xn a-
x a
n , }) {f(xn L- n .
-Cauchy ) f(x
) ,x=a , , x=a( , L ) f(x x
,a- >0 >0 0<|x-a|< .|f(x)-L|<
x- - ) f(x
,x=a L ) f(x x ,
>0 E x>E .|f(x)-L|<
x- a - - ) f(x
,x=a ) f(x x ,a - M>0
>0 0<|x-a|< .f(x)>M
x- - ) f(x
= ) , ( 0, ) f(x x ,
M>0 D x>D .f(x)>M
- ) f(x
) x=a ) ,((a,a+ L )f(x
x ) a+- ( , >0 >0
(a,a+)x .|f(x)-L|<
- ) f(x ,x=x0
f(x)- x=x0 :
.1 .x=x0
.2 x=x0 .(f(x0)) x=x0
- ) f(x ,x=x0 f(x)-
x0- :
.1 .x=x0
.2 x=x0 .(f(x0)) x=x0

:
.1 - ) f(x ,x=x0
x0- :
( .x=x0
( x=x0 ,x=x0 f(x)-
.x=x0
.2 )( - ) f(x
,x=x0 x0-
x=x0 , .
.3 )( - ) f(x
,x=x0 x0-
x=x0 ) , (.
:
.1 " " .

## ( gx( xa) ) = B , lim

c , lim
x ( fa ( x) ) = A .2
x a
x a
lim(chf(x))=chA
lim(f(x)+g(x))=A+B
lim(f(x)hg(x))=AhB
,B 0 ) lim(f(x)/g(x))=A/B a ( g(x) 0
.3 ' h(x) ,g(x) ,f(x) - .x=a
x ) .h(x)>f(x)>g(x
,lim(h(x))=lim(g(x))=L .lim(f(x))=L
.4 ) f(x ,a ) g(x 0 x a -:
lim(f(x)hg(x))=0
sin( x)
) lim (

= 1 .5
x 0
x

.6 ) f(x ,x=a ( f ( x) ) = L
, lim
x a
a ) f(x.

## .7 ) f(x ,x=a lim ( f ( x) ) = L

x a

, L 0 -:
L>0 f(x)>0 .x
L<0 f(x)<0 .x
.8 ) f(x x=a
.x=a-
.9 ) , , ,,
(f(x)=c, f(x)=x, f(x)=ax (a>0), f(x)=sinx :
.
g(x) ,f(x) .10 c ,x0-
) chf(x x0-
) f(x)+g(x x0-
) f(x)hg(x x0-
f(x)/g(x) ,g(x0) 0 x0-
f(x) .11 x0- .x0-
f(x) .12 ] .[a,b ,f(a)hf(b)<0
,a<c<b .f(c)=0-
[a,b] .13

] f: [a,b ] .[a,b

,a<c<b ) f(c)=c - (.
.14 f(x) -Cauchy ] y0 ,[a,b
) f(a .f(b)- ,a<c<b .f(c)= y0 -
.15 -Weierstrass ) f(x ] ,[a,b ) f(x ,
.

f '( x0 ) = lim

x x0

f ( x) f ( x0 )
f ( x + h) f ( x )
f ' ( x ) = lim
:
h0
h
x x0

( f ( x) g ( x) ) =

f '( x) g '( x)

( c f ( x) ) = c f '( x)
( f ( x) g ( x) ) =

f '( x) g ( x) + f ( x) g '( x)

f ( x) f '( x) g ( x) f ( x) g '( x)
, g ( x) 0

=
g 2 ( x)
g ( x)

dy dy dx
: h(t0 ) = f ( g ( x) ) = f '( x0 ) g '(t0 ) :
=

dt dx dt

c' = 0
x' =1
(ax) ' = a
( x n ) ' = nx n 1

## ( sin( x) ) ' = cos( x)

( cos( x) ) ' = sin( x)
1
cos 2 ( x)
1
cot( x) = 2
sin ( x)
1
ln( x) =
x
x
(a ) ' = a x ln(a )
tan( x) =

(e x ) ' = e x

( arcsin( x) ) ' =

1 x2
1
( arccos( x) ) ' =
1 x2
1
( arctan( x) ) ' =
1 + x2

. x0 f ' ( x0 ) *
y y0 = f ' ( x0 ) ( x x0 ) : ,

:
.1 ) f(x ' ,x0 . : ) f(x ,x0-
.
.2 -Fermat ) f(x ) ,(a,b
.(a,b)x0 ) f(x x0 ,(a,b)-
.f l(x0)=0
.3 -Rolle ) f(x ] ,[a,b :
) f(x ].[a,b
) f(x ).(a,b
)f(a)=f(b
(a,b)c .f l(c)=0 -
.4 -Lagrange ) f(x ] ,[a,b
:
) f(x ].[a,b
) f(x ).(a,b
(a,b)c ).f l(c)=[f(b)-f(a)]/(b-a
.5 -Cauchy ) g(x) ,f(x
] ,[a,b :
) g(x) ,f(x ].[a,b
) g(x) ,f(x ).(a,b
0 g l(x) - .(a,b)x
a<c<b ]).f l(c)/g l(c)=[f(b)-f(a)]/ [g(b)-g(a
.6 - ) f(x ) ,(a,b:
) f(x ) f l(x)>0 (a,b )(a,b
) f(x ) f l(x)<0 (a,b )(a,b
) / ] [f l(x)>0(.

10

0
0

.7 - " " :
) g(x) ,f(x ,x=a , , a- ,
:
lim ( f ( x) ) = lim ( g ( x) ) = 0
x a

x a

f ( x)
lim

) x a g ( x

f ( x)
f ( x)
f ( x)
lim
lim
= lim

)xa g ( x
)x a g ( x

xa g ( x)
:
x a + . x a
x . x
) g(x) ,f(x , ( a, ) - x
f ( x)
f ( x)
lim
= lim

) x g ( x

x g ( x)

" ":
) g(x) ,f(x ,x=a , , a- , :
lim ( f ( x) ) = lim ( g ( x) ) = 0
x a
x a

f ( x)
lim

) x a g ( x

g ( x) 0 x a
f ( x)
f ( x)
=
lim
lim
x a
)xa g ( x

g ( x)

:
x a . x a
x . x
+

11

: .8
f ( x) = f (a ) +

f ( a )
f ( a )
f ( n ) (a)
2
n
( x a) +
( x a) + +
( x a ) + Rn ( x)
1!
2!
n!

f ( n +1) (c)
n +1
Rn ( x) =
( x a)
(n + 1)!

:
x 2 x3 x 4
+ + +
2! 3! 4!
x3 x5 x 7
sin( x) = x + +
3! 5! 7!
x2 x4 x6
cos( x) = 1 + +
2! 4! 6!
x3 x5 x 7
arctan( x) = x + +
3 5 7
x 2 x3 x 4
ln( x + 1) = x + +
2 3 4
1
= 1 + x + x 2 + x3 +
1 x

m(m 1) (m k + 1) k
m
1
1
x
x
+
=
+
( )

k!
k =1
ex = 1 + x +

12

dx = x + c
n
x dx =

x n +1
+c
n +1

## sin( y ( x )) y' ( x )dx = cos( y ( x )) + c

cos( y ( x )) y ' ( x )dx = sin( y ( x ))

y ' ( x )dx
= ln | y ( x ) | + c
y( x)

e dx = e
x

+c

y' ( x)
dx = cot( y ( x )) + c
2
( y ( x ))
y' ( x)
cos2 ( y ( x )) dx = tan( y ( x )) + c
1
y' ( x)
y( x)
a 2 + y 2 ( x ) dx = a arctan( a ) + c
y( x)
y' ( x)
a 2 y 2 ( x ) dx = arcsin( a ) + c

sin

y( x)
a y ' ( x )dx =

a y( x)
+c
ln(a )

( f ( x) g ( x) ) dx = f ( x)dx g ( x)dx
a f ( x)dx = a f ( x)dx
f ( x) g '( x)dx = f ( x) g ( x) f '( x) g ( x)dx
f ' ( g ( x) ) g '( x)dx = f ( g ( x) ) + c

13

T (c1 , c2 , , cn ) = f (ci ) xi :
i =1

,x- ] ,[a,b . n
T : a = x0 < x1 < x2 < < xn 1 < xn = b ].[a,b
= xi ] ci , xi xi 1 = [ xi 1 , xi ] ci [ xi 1 , xi

} (T ) = max {x1 , x2 , , xn .

:
] [a,b
n

f ( c ) x
i

i =1

## I = lim T (c1 , c2 , , cn ) = lim

(T ) 0

(T ) 0

) T , {ci } - (0-
> 0 , n N T ] ,[a,b , (T ) <

} {ci

I f (ci ) xi <
i =1

:
.1 ] [a,b , :
i (b a ) b a

n n

f ( x)dx = lim f a +
i =1

) c dx = c(b a
a

.2 :
[a,b]- ) [a,b]- (.
. ,
.
a

f ( x)dx = 0
a

f ( x) dx = f ( x )dx
a

14
b

c f ( x)dx = c f ( x)dx

a
c

a
b

( f ( x) g ( x) ) dx = f ( x)dx g ( x)dx
a

## f ( x)dx = f ( x)dx + f ( x)dx

.3 ) f(x' ,[a,b]- m f ( x) M - ] x [ a, b
b

) m ( b a ) f ( x ) dx M ( b a
a

.4 ) f ( x) g ( x

f ( x)dx g ( x)dx

.5 : ) f(x ,[a,b]- ] c [ a, b
b

) f ( x)dx = f (c) ( b a
a

## .6 " f(x) : ,[a,b]- ) f(x -

] c [ a, b ] .[a,t , ],[a,b
x

, F :[a, b] R F ( x) = f (t ) dt ) f(x.[a,b]-
c

) g (x

f (t )dt = f ( g ( x) ) g ( x) :
a

b

F ( x) | :
a

b

## , m f ( x ) M , g ( x ) 0 - m g ( x )dx ( f ( x) g ( x) )dx M g ( x)dx

15

:
) f(x' ( , ) /( , a ] /[a, ) -

## f ( x)dx = lim f ( x)dx

a

f ( x) dx + f ( x)dx
c

) ( ," . -

= f ( x)dx

:
f(x)- ,[a,b)- ,b- f(x)-
b

] >0) [a,b-( .

f ( x)dx

, f ( x )dx

lim+

f ( x)dx

' :(a,b]-

f ( x)dx

a+

. f ( x)dx = lim
0

) f(x c

f ( x)dx

f ( x)dx
c

## , f ( x)dx. f ( x)dx = f ( x)dx + f ( x)dx :

16

:
:

dx

du
p

, > 1 1

dx

ln 2

) x ( ln x

, p > 1 p 1

.1 ) f(x g(x)- [ a, ) - , [ a, b] -
) , f ( x) g ( x:

g ( x)dx

f ( x)dx

f ( x)dx

g ( x )dx .

)f ( x
.2 : ) f(x g(x)- , = L
)g ( x

## < f ( x)dx 0 < L g ( x)dx -

L = 0

g ( x)dx

= L

lim

f ( x)dx

f ( x)dx

g ( x)dx

.3 ) f(x ] ,[a,b a . f ( x ) dx

f ( x)dx

)=( , , .

) (

## .4 f(x) :Abel g(x)- .

f ( x)dx

g(x)-

( f ( x) g ( x) )dx

## .5 f(x) : g(x)- . b [a, ) ,M

f ( x)dx M
a

g(x) , ,g ( x ) = 0 -
, lim
x

( f ( x) g ( x) )dx
a

17

## {an } n=1 . -n-:

n

. S n = ak = a1 + a2 + + an
k =1

n =1

} : {S n

a1 , a1 + a2 , a1 + a2 + a3 , .
) ( S n = S
, lim
n

a
n =1

.S-. an = S :
n =1

.1 an > 0 , an n-.
n =1

n
.2 ) ( . an > 0 , ( 1) an
n =1

.3 .
.4 x n

,R , . x < R

n =1

) = R .( R = 0 ) , ( R, R
.
:

.1 :Cauchy

a
n =1

" >0 N ,

n>N k . S n + k S n < :

.2

b ,a
n =1

n =1

c , . :

n =1

n =1

. ( an bn ) , c an
.3 an = 0
. lim
n

.4

a
n =1

a
n =1

)=(.

18

.5 an an = 0 -
. lim
n

.6 D'Alembert) :(Cauchy -
an +1 1
1
=
, lim
R
R n an

= lim n an
n

.7 : ) f(x , ( R, R ) -
f ( k ) (0) k
M>0 f ( k ) (0) < M - ,k x
!k

= )f ( x
k =1

) , 0- n- (

:
:

aq

q < 1

n =1

) ( ln n

, > 1 . , < 1

n =1

, = 1 > 1 1
:
.1 an bn:

n =1

an .
n =1

n =1

bn
.2 = L
an

n =1

( bn 0 ) lim:
n

<0< L

a
n =1

L = 0

= L

n =1

bn - .
n =1

an ,

a
n =1

n =1

n =1

19

an +1
.3 = L
an
0 L < 1 .
L > 1 .
L = 1 .
.4 : lim n an = L:
n

lim:
n

0 L < 1 .
L > 1 .
L = 1 .
.5 an : f(x) , , , -

) , [1, f ( n) = an

f ( x)dx
1

.6 = n an
, lim
n

.7

) (a
n

n =1

n =1

a
n =1

a
n =1